Analysis Of Leadership Style and Corporate Culture on Employee Behavior and Performance Case Study: PT. Paragon Teknologi dan Innovasi (PTI) - Markhamah, Siti; Sopiah; Ludi Wishnu Wardana (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of leadership style, corporate culture, and career development on employee performance at PT Paragon Technology Innovation (PTI) Indonesia. The research sample consisted of 99 samples taken from a population of around 12,000 employees using random sampling method analyzed using SPSS 25 statistical software. The results of the analysis showed that the three variables had a significant influence on employee performance. Transformational leadership style increases motivation and work spirit, while positive corporate culture encourages engagement and commitment. In addition, effective career development programs contribute to increased skills and job satisfaction. This study emphasizes the importance of synergy between leadership style, corporate culture, and career development in creating an optimal work environment. These findings provide recommendations for PTI management to continue developing these three elements in order to improve employee performance and support the overall success of the organization